(untitled) (American Journal of Islam and Society, 2007)
This first-ever conference convened by the Champa peoples, of whom the Cham (both Muslim and non-Muslim) are an important component, focused on the “Sociocultural Issues of Champa 175 Years after Its Disappearance (1832-2007).” Held on 7-8 July 2007, in San Jose, CA, it was opened by Chuck Reed (mayor, San Jose), Musa Porome (chairman, Organizing Committee), Ahmad Yahya (Member of Parliament, Cambodia; founder, Radio SapCham [Voice of the Cham]), and R. Obleo (a representative of the Champa people of the Central Highlands, Vietnam, now living in America). Session One, “Language and Culture,” moderated by Mohammad Zain Bin Musa (University Kebangsaan Malaysia), began with Marc Brunelle (University of Ottawa, Canada), who spoke on “Diglossia, Bilingualism, and Literacy: Can Eastern Cham Be Revitalized?” Brunelle, a fluent Cham and Vietnamese speaker, touched upon a core problem; the Cham language has not developed enough to accommodate modernity. Thus, the eastern Cham are generally bilingual, the formal language is limited to important events, the spoken language contains many Vietnamese words, regional pronunciations have appeared, Cham-language written literature is very rare, and the community (traditionally) has opposed the script’s romanization. He sees two choices to ensure its survival: romanize or simplify the script. David G. Sox (United States Coast Guard Pacific Command, Oakland, CA) presented “Toward a Book/CD-ROM of the Culture and Customs of Ancient Champa and Modern Champa Peoples.” He is seeking the community’s active participation in documenting Champa’s geography, prehistory ...